Chronic Pulmonary Silicone Embolism from Breast Augmentation Is Not a Common Finding in Explanted Lungs. (15th March 2018) - Singh, Jarmanjeet; Inaty, Hanine; Mukhopadhyay, Sanjay; Mehta, Atul C.
Abstract : Objective . Acute pulmonary silicone embolism (APSE) related to subcutaneous silicone injections is a well-known entity. Recently, a few cases of pathologically confirmed chronic pulmonary silicone embolism (CPSE) from breast implants have been reported. The prevalence of CPSE in women with breast augmentation is unknown. This study was done to determine the prevalence of CPSE in female lung transplant recipients with a history of breast augmentation and to determine whether breast augmentation plays a role in chronic lung diseases requiring lung transplantation. Methods . A retrospective chart review was performed to identify female lung transplant recipients with a history of breast augmentation prior to or at the time of lung transplantation. Ten patients meeting these criteria were identified. The pathologic features of the explanted lungs of these patients were reexamined for CPSE by a board-certified pathologist with expertise in lung transplantation and pulmonary embolism. Results . Of 1518 lung transplant recipients at Cleveland Clinic, 578 were females. Of 578 females, 10 (1.73%) had history of breast augmentation. A total of 84 H&E-stained slides from the explanted lungs from 10 cases were examined. No pathologic evidence of chronic silicone embolism was seen in any of the 10 cases. Conclusions . CPSE is not associated with pulmonary disease leading to lung transplantation. Breast augmentation is not a significant contributor to pulmonary disease requiring lung transplantation. Further studies are required to ascertain the prevalence of CPSE in the general breast augmentation populace and to define the relationship between breast augmentation and pulmonary disease.